Լրատվամիջոցների արտադատական և դատական պաշտպանությունը ԼՂՀ-ում - Մարդյան, Գ.
В данной статье анализируются особенности эффективных средств правовой защиты журналиста в Арцахе, изучается международный опыт и сверхзадачи по защите прессы, как одного из важнейших общественных институтов. В теме излагаются конституционные и законодательные гарантии свободы слова, в частности, законы «О защите прав человека», «О массовой информации», «О свободе информации», «О телевидении и радио» и дополнителные правовые докумнты. The article discusses the choice of the effective means of the legal protection of a journalist in Artsakh, the research of the international experience and the ultimate issue of the protection of the press as one of the most important social institutes. In the article the constitutional and legislative guarantees of speech freedom, the laws: concerning "On the protection of human rights", "Mass Media""Freedom of information", "TV and Radio" and supplementary legal documnets are analyzed.
Keywords: Լրագրություն